FAKTOR- FAKTOR YANG MEMENGARUHI PERILAKU IBU DALAM PEMBERIAN SARAPAN PAGI PADA ANAK DI SD ST.THOMAS 1 MEDAN TAHUN 2013 - Rindika Christiani; Eddy Syahrial; alam bakti (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
Breakfast is the food and drink that provide energy and other nutrientsthat were consumed in the morning. Breakfast is human need that should beregularly. Humans need to have breakfast,because it use to supply the sufficiencyof energy for daily activities. If you don’t have itt, your body will not have energyto do your activity.This study was aimed to determine factors that influence mother behaviorin the provision of breakfast to children in elementary school of St.Thomas 1Medan. Some factor that influence were age, education, employment, knowledgeand attitude. This research was a quantitative analytic study. The population ofthis study were all of students in St. Thomas 1 elementary school and 85 mothersof the student. The sampling technique was using stratified random sampling. Thedata was obtained by questionnaires and interviews and analyzed used Chi-Square test.The research results showed that there was no correlation (p> 0.05)between age, education, employment and mother’s behavior on giving breakfastand there was a correlation (p <0.05) between knowledge, attitude and mother’sbehavior on giving breakfast.As recommendation in this study, the parents should give more attentionand increase nutrition needs, especially in its quality and breakfast behavior oftheir children.